2019
DOI: 10.1002/nau.24024
|View full text |Cite
|
Sign up to set email alerts
|

Are EAU/ESPU pediatric urology guideline recommendations on neurogenic bladder well received by the patients? Results of a survey on awareness in spina bifida patients and caregivers

Abstract: Aims The Paediatric Urology Guidelines Panel reports initial experience with patient involvement in spina bifida patient groups to gather information on their awareness of the guidelines and reflection of guideline recommendations. Methods The survey was delivered to spina bifida patients/parents via the national society groups in Turkey, Germany, and The Netherlands. Questions included demographic features, medical status, awareness, and agreement on the recommendations given in the guidelines and future expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A recent survey in 291 patients from three countries with a mean age of 13.9 ± 12.2 years, demonstrated that medication was taken by 78% of patients (64% anticholinergics) and complete dryness rates for urine and stool were 24% and 47%, respectively . A recent systematic review concerning the outcome of adult meningomyelocele patients demonstrated that around 37% (8‐85%) were continent, 25% had some degree of renal damage and 1.3% end‐stage renal failure .…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey in 291 patients from three countries with a mean age of 13.9 ± 12.2 years, demonstrated that medication was taken by 78% of patients (64% anticholinergics) and complete dryness rates for urine and stool were 24% and 47%, respectively . A recent systematic review concerning the outcome of adult meningomyelocele patients demonstrated that around 37% (8‐85%) were continent, 25% had some degree of renal damage and 1.3% end‐stage renal failure .…”
Section: Introductionmentioning
confidence: 99%
“…16 Dogan HS et al reported 24% and 47% of dryness for urine and stool respectively from patients of three countries. 17 There are several guidelines and timetables for evaluation schedule of neuropathic bladder patients. European Association of Urology (EAU)/European Society of Pediatric Urology (ESPU) guidelines recommend proactive management with CIC AE anticholinergic medication starting in the first months of life.…”
Section: Discussionmentioning
confidence: 99%
“…Dogan HS et al . reported 24% and 47% of dryness for urine and stool respectively from patients of three countries 17 …”
Section: Discussionmentioning
confidence: 99%